Creative and Adaptive Marketing Strategies among Wedding Vendors: Evidence from West Jakarta - Marlina Marlina; Angel Lorenza Alexis; Fangela Myas Sari (Journal of Social and Policy Issues, 2025)
This study aims to analyze creative and adaptive marketing strategies implemented by wedding vendors in West Jakarta in response to increasingly competitive market dynamics. Specifically, the research seeks to examine how marketing strategies can address business challenges, enhance competitiveness, and support long-term sustainability within the wedding service industry. Employing a qualitative research approach, this study investigates four wedding vendors—Awen Catering, Ohana Enterprise, Alfa Kreasi, and David Entertainment—as the main research objects. Data were collected through in-depth interviews, observations, and documentation, and subsequently analyzed using SWOT analysis to identify internal strengths and weaknesses as well as external opportunities and threats. The findings reveal that creativity and innovation in service offerings, high service quality, professional work practices, flexibility in responding to client needs, and the ability to adapt to competitive pressures are key determinants of effective marketing strategies. Moreover, the vendors’ capacity to identify market opportunities and deliver positive customer experiences significantly enhances brand awareness, customer trust, and market reach. The SWOT-based analysis demonstrates that adaptive marketing strategies enable wedding vendors to mitigate risks, overcome operational challenges, and strengthen their competitive positioning. In conclusion, the study highlights that well-designed, creative, and adaptive marketing strategies are essential for improving sales performance, sustaining customer relationships, and ensuring the long-term viability of wedding vendors in West Jakarta.